Effect of aggregate structure on load-carrying capacity and deformation resistance of porous asphalt concrete based on discrete-element modelling. Issue 11 (19th September 2022) - Zhu, Junqing; Ma, Tao; Lin, Zihao; Zhu, Haoran
ABSTRACT: Porous asphalt concrete (PAC) constitutes large air voids and coarse aggregate, forming a unique aggregate structure. The open pore structure is advantageous in creating space for stormwater runoff to infiltrate into an underground basin and reduce tyre-road noise. However, this aggregate structure compromises the load-carrying capacity and deformation resistance of the mixture. Achieving balance between permeability and bearing capacity of PAC has been a major concern. This study evaluates effects of the aggregate structure on bearing capacity and the deformation resistance of PAC. Gradation-based framework was first applied to examine different gradations of PAC. Discrete-element models of PAC with varying gradations were developed to evaluate its performance and characteristics of aggregate skeleton. A laboratory wheel track test was conducted to validate findings from the DEM analysis. It was found that gradation that meets the interlock check of the framework produced a mixture with optimal performance. More coarse aggregate provides additional strength but lacks sufficient smaller-sized particles to form a new skeleton when it breaks down. More fine aggregate diminishes the load-carrying capacity and deformation resistance of the mixture as no stable skeleton could be formed.